Hydrogen Bonding and Transfer in the Excited State 2010
DOI: 10.1002/9780470669143.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Electronic‐Excited‐State Structures and Properties of Hydrated DNA Bases and Base Pairs

Abstract: Computational chemistry methods have been established as an attractive and reliable alternative to the costly and time-consuming experiments used to determine structures, properties and reactivities of molecular species. Although the modelling of the exact environmental conditions at the high theoretical level is still very expensive and may not be possible in several cases, computational methods are capable of providing reliable predictions in many ways, which can be useful to experimentalists and to the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 181 publications
(289 reference statements)
0
2
0
Order By: Relevance
“…It is reported that [N 4 4 4 4 ][NTf 2 ] has a melting point of 365−369 K, 45,46 determining its crystallized nature at room temperature, possibly due to the predominant Coulombic force between cation and anion. 47 [NTf 2 ] − anion was selected originally from an expectation of increasing CO 2 uptake because of the fluorinated methyl groups which have good affinity with CO 2 molecules by electrostatic forces. 48 Based on the amorphous cell module, a cell containing 30 ionic liquid molecules was built.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that [N 4 4 4 4 ][NTf 2 ] has a melting point of 365−369 K, 45,46 determining its crystallized nature at room temperature, possibly due to the predominant Coulombic force between cation and anion. 47 [NTf 2 ] − anion was selected originally from an expectation of increasing CO 2 uptake because of the fluorinated methyl groups which have good affinity with CO 2 molecules by electrostatic forces. 48 Based on the amorphous cell module, a cell containing 30 ionic liquid molecules was built.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the superiority of solid-state ionic liquids and avoidance of water influence, a hydrophobic and solid-state ionic liquid, [N 4 4 4 4 ]­[NTf 2 ] (MW = 522.61 g mol –1 ) with a symmetric cation (see Figure ), was used to trap CO 2 and CH 4 in a small scale. It is reported that [N 4 4 4 4 ]­[NTf 2 ] has a melting point of 365–369 K, , determining its crystallized nature at room temperature, possibly due to the predominant Coulombic force between cation and anion . [NTf 2 ] − anion was selected originally from an expectation of increasing CO 2 uptake because of the fluorinated methyl groups which have good affinity with CO 2 molecules by electrostatic forces .…”
Section: Methodsmentioning
confidence: 99%